Analisis Kalimat Dalam Siniar Spotify Merry Riana Periode Oktober-November 2019 - Ellisa Ivana Dea; I Wayan Pastika; Ni Putu N. Widarsini (Stilistika : Journal of Indonesian Language and Literature, 2021)
The topic of this article is "Sentence analysis in Merry Riana's Spotify broadcast for the period October-November 2019". As the background of this study is that, in the 41 broadcast episodes chosen, Merry uses modern Indonesian, making it easier for the researchers to review when this analysis is carried out. Second, research on Merry Riana's spotify siniar with sentense structure has never been done. Third, this study may be motivating and increasing researchers' insight. In this study, two research questions were raised, namely what types of sentences are contained in Merry Riana's spotify podcast and how is the structure of the sentence function filler in Merry Riana's spotify podcast. The purpose of this study is to find out the types of sentences contained in Merry Riana's spotify podcast and to find out how the structure of the filler function is. Qualitative and quantitative descriptive study which is presented in the form of data excerpts containing sentences and table of data percentage. In the data collection method, observation supported by listening technique followed by note-taking techniques were applied. The results of this research data analysis are presented in formal and informal methods. The results of this study obtained eight types of sentences, namely single sentences, compound sentences, declarative sentences, interrogative sentences, imperative sentences, exclamative sentences, complete sentences, and incomplete sentences. In this study, it is also found 23 variations of syntactic functions consisting of seven variations of single sentences and 16 variations of compound sentences.